(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the characteristics of iron deficiency anemia and some related factors in children under 5 years old treated at Phu Xuyen General Hospital in 2023. Subjects and methods: Cross-sectional descriptive study design conducted at Phu Xuyen General Hospital on 88 children under 5 years old treated as inpatients from May to October 2023. Results: The rate of iron deficiency anemia was 28.4%, mainly in the age group of 6-24 months (52%). Mild anemia accounted for 60%, moderate anemia 40%. Pale skin (48%) and anorexia (40%) were common clinical manifestations. Average hemoglobin value 100.8 g/l, MCV 74.0 fl, serum Fe 6.2 mmol/l. Child is second child or above, currently underweight, not supplemented with micronutrients/iron had a higher rate of anemia but not statistically significant. Mother’s education level from high school or below was the only factor that had a statistically significant association (p < 0.05). Conclusion: Iron deficiency anemia in children under 5 years old is still common and is related to maternal education. It is necessary to strengthen nutritional interventions and health education for parents, especially high-risk groups.